Uterine Nodal expression supports maternal immunotolerance and establishment of the FOXP3+ regulatory T cell population during the preimplantation period - Yull, Sarah; Shafiei, Shiva; Park, Craig B.; Kazemi, Parinaz; Tiemann, Emily B.; Pagé, Marie-Hélène Godin; Dufort, Daniel (Frontiers in Immunology, 2023)
Pregnancy success is dependent on the establishment of maternal tolerance during the preimplantation period. The immunosuppressive function of regulatory T cells is critical to limit inflammation arising from implantation of the semi-allogeneic blastocyst. Insufficient maternal immune adaptations to pregnancy have been frequently associated with cases of female infertility and recurrent implantation failure. The role of Nodal, a secreted morphogen of the TGF superfamily, was recently implicated during murine pregnancy as its conditional deletion (Nodal / ) in the female reproductive tract resulted in severe subfertility. Here, it was determined that despite normal preimplantation processes and healthy, viable embryos, Nodal / females had a 50% implantation failure rate compared to Nodal loxP/loxP controls. Prior to implantation, the expression of inflammatory cytokines MCP-1, G-CSF, IFN-𝛾 and IL-10 was dysregulated in the Nodal / uterus. Further analysis of the preimplantation leukocyte populations in Nodal / uteri showed an overabundance of infiltrating, pro-inflammatory CD11b high Ly6C + macrophages coupled with the absence of CD4 + FOXP3 + regulatory T cells. Therefore, it is proposed that uterine Nodal expression during the preimplantation period has a novel role in the establishment of maternal immunotolerance, and its dysregulation should be considered as a potential contributor to cases of female infertility and recurrent implantation failure.